The Effect of Sense of Belonging on Homesickness in Rantau Students in Makassar City - Barwin, Adinda; Zainuddin, Kurniati; Irdianti, Irdianti (Polteknik Ilmu Pemasyarakatan, 2024)
Homesickness is one of the negative emotions experienced by individuals, which tends to increase when they move from one place to another. This feeling is commonly felt by students who are studying in a different city, causing them to be far from familiar places and their families. They must learn to be independent, cope with feelings of longing, and adjust to a new environment. These students also face challenges in their educational processes that differ from those of students who do not move away from home. Therefore, students need to adapt to their surroundings to be accepted and to feel a sense of belonging. In short, students who are away from home need to have a sense of belonging.This research aims to determine the effect of sense of belonging on homesickness among students in Makassar. The sample for this study used accidental sampling techniques, with a total of 198 subjects. This study employed a quantitative method with simple regression analysis. The results indicate that there is a significant effect of sense of belonging on homesickness among students in Makassar, with a significance level of (0.00 < 0.05). The R-Square model is -0.337, meaning that sense of belonging influences homesickness by 33.7%, while 66.3% is influenced by other factors. The implications of this research serve as a reference that can contribute to others regarding sense of belonging and homesickness.